Climate History of Southern Mongolia Since 17 ka: The Ostracod, Gastropod and Charophyte Record From Lake Ulaan - Mischke, Steffen; Lee, Min Kyung; Lee, Yong Il (Frontiers in Earth Science, 2020)
Late glacial and Holocene environmental and climate change in the Gobi Desert is poorly understood due to the lack of appropriate geological archives and commonly faced difficulties in establishing reliable chronologies. Here, the relatively well-dated sediment record from the terminal Lake Ulaan is used to reconstruct the lake history and climate in the region. Most abundant calcareous fossils in the lake sediments are ostracod (micro-crustacean) valves. The ostracod assemblage is dominated by Limnocythere inopinata, and generally very shallow conditions and sodium-dominated waters are inferred for Lake Ulaan. A single period of significantly increased silt accumulation in the late glacial was recorded at ca. 16 ka, probably as a result of melting glaciers in the uppermost reaches of the lake’s main tributary, the Ongin River, and the influx of glacially-ground, fine materials. Lake Ulaan had a higher salinity afterwards during the Greenland Interstadial 1, and dry climate prevailed in the region. The lake level started to rise and the salinity decreased since ca. 12.3 ka, leading to the establishment of freshwater conditions in the early Holocene. Highest inflows and highest productivity in and around the lake, and wettest climate conditions in the region were recorded in the early Holocene. Lake conditions, most favourable for the aquatic fauna, culminated ca. 10 ka. Afterwards, Lake Ulaan experienced a step-wise lake-level decline and salinity increase at 9.4 and 6.8 ka. The further shrinkage of the lake and the approaching Ongin River mouth near the central part of the basin is recorded since 3.2 ka.